Advanced Research in Porcine Reproductive and Respiratory Syndrome Virus Co-infection With Other Pathogens in Swine - Zhao, Dengshuai; Yang, Bo; Yuan, Xingguo; Shen, Chaochao; Zhang, Dajun; Shi, Xijuan; Zhang, Ting; Cui, Huimei; Yang, Jinke; Chen, Xuehui; Hao, Yu; Zheng, Haixue; et al. (Frontiers in Veterinary Science, 2021)
The porcine reproductive and respiratory syndrome virus (PRRSV) is the pathogen causing epidemics of porcine reproductive and respiratory syndrome (PRRS), and is present in every major swine-farming country in the world. Previous studies have demonstrated that PRRSV infection leads to a range of consequences, such as persistent infection, secondary infection, and co-infection, and is common among pigs in the field. In recent years, coinfection of PRRSV and other porcine pathogens has occurred often, making it more difficult to define and diagnose PRRSV-related diseases. The study of coinfections may be extremely suitable for the current prevention and control in the field. However, there is a limited understanding of coinfection. Therefore, in this review, we have focused on the epidemiology of PRRSV coinfection with other pathogens in swine, both in vivo and in vitro.